Mechanisms influencing the coexistence of multiple consumers and multiple resources: resource and apparent competition. Issue 1 (27th August 2018) - McPeek, Mark A.
Abstract: Interactions among multiple resources and consumers involve two indirect interactions: resource competition among consumers and apparent competition among resources. However, competition among multiple consumers is typically viewed through the lens of direct interactions embodied in the Lotka‐Volterra competition model, which fails to capture the mechanisms of these indirect interactions. In this paper, I analyze various elaborations of MacArthur's and Tilman's original consumer–resource models including more than two species per trophic level, saturating functional responses, and direct intraspecific density dependence within the consumers. First, the simplest model with two resources and two consumers with linear functional responses is analyzed via the structure of the resulting isoclines, and this is reconciled with Tilman's graphical ZNGI/consumption vector approach. With three species at each trophic level even in this simple model, each consumer is not required to have the largest impact on the resource that most limits its growth for multiple consumers to coexist. In fact, a consumer that is an inferior competitor on each resource in isolation may still coexist with superior competitors, and conversely a consumer that is an inferior competitor on each available resource may still be able to drive all other consumers extinct. However, the maximum number of coexisting consumers is set by the number of available resources. Saturating functional responses do not qualitatively alter the conditions for multiple consumers and resources to coexist at a stable point equilibrium but do increase the range of apparent competitive abilities for resources that can invade and coexist. Saturating functional responses also increase the range of dynamics that the community may display (i.e., limit cycles and chaos), which previous analyses have shown can permit more consumer species than resources to coexist. Adding direct intraspecific density dependence in the consumers, either in the form of feeding interference or density‐dependent demographic rates, permit more consumers to coexist than available resources, even at stable point equilibria. Understanding the indirect effects that cascade through a community is essential to predicting community changes and understanding how species at multiple trophic levels coexist, and these indirect effects should not be shrouded behind the curtain of Lotka‐Volterra competition.